The homologous homeodomain-leucine zipper transcription factors HaHB1 and AtHB13 confer tolerance to drought and salinity stresses via the induction of proteins that stabilize membranes - Cabello, Julieta Virginia (2012)
Transgenic approaches to conferring tolerance to abiotic stresses have mostly resulted in some degree of plant yield penalty under normal or mild stress conditions. Recently, we have reported that the homeodomain-leucine zipper transcription factors (TFs) HaHB1 and AtHB13 were able to confer tolerance to freezing temperatures via the induction of glucanase (GLU and PR2) and chitinase (PR4) proteins. In the present study, we show that the expression of these TFs, as well as that of their putative targets AtPR2, AtPR4 and AtGLU, is up-regulated by drought and salinity stresses. Transgenic plants overexpressing separately these five genes exhibited tolerance to severe drought and salinity stresses, displaying a cell membrane stabilization mechanism. Under normal or mild stress conditions, these plants achieved an improved yield associated with higher chlorophyll content. Moreover, overexpression of the sunflower HaHB1 gene from its own, inducible, promoter conferred a high drought-stress tolerance without yield penalty under normal or mild stress conditions. We propose these TFs as potential biotechnological tools to breed crops for tolerance to multiple stresses and for increased yield. © 2012 The Authors. Plant Biotechnology Journal © 2012 Society for Experimental Biology, Association of Applied Biologists and Blackwell Publishing Ltd.